2020
DOI: 10.7554/elife.61245
|View full text |Cite
|
Sign up to set email alerts
|

Atg43 tethers isolation membranes to mitochondria to promote starvation-induced mitophagy in fission yeast

Abstract: Degradation of mitochondria through mitophagy contributes to the maintenance of mitochondrial function. In this study, we identified that Atg43, a mitochondrial outer membrane protein, serves as a mitophagy receptor in the model organism Schizosaccharomyces pombe to promote the selective degradation of mitochondria. Atg43 contains an Atg8-family-interacting motif essential for mitophagy. Forced recruitment of Atg8 to mitochondria restores mitophagy in Atg43-deficient cells, suggesting that Atg43 tethers expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…Aiming to evaluate the physiological roles of these negative regulatory mechanisms toward TORC1 activity, we turned our attention to autophagy, which is induced by TORC1 inactivation during nutritional starvation ( Kohda et al, 2007 ). Autophagic degradation of GFP-tagged phosphoglycerate kinase (Pgk1) has been successfully used as a quantitative readout of autophagy ( Welter et al, 2010 ; Fukuda et al, 2020 ); upon autophagy induction, Pgk1-GFP is transported from the cytoplasm to vacuoles for degradation, but the GFP moiety remains undigested due to its resistance to the vacuolar proteases. Thus, the cellular autophagic activity in response to starvation can be monitored by immunoblotting to detect the free GFP released from Pgk1-GFP ( Figure 4—figure supplement 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Aiming to evaluate the physiological roles of these negative regulatory mechanisms toward TORC1 activity, we turned our attention to autophagy, which is induced by TORC1 inactivation during nutritional starvation ( Kohda et al, 2007 ). Autophagic degradation of GFP-tagged phosphoglycerate kinase (Pgk1) has been successfully used as a quantitative readout of autophagy ( Welter et al, 2010 ; Fukuda et al, 2020 ); upon autophagy induction, Pgk1-GFP is transported from the cytoplasm to vacuoles for degradation, but the GFP moiety remains undigested due to its resistance to the vacuolar proteases. Thus, the cellular autophagic activity in response to starvation can be monitored by immunoblotting to detect the free GFP released from Pgk1-GFP ( Figure 4—figure supplement 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it remains unknown whether the ATG32–ATG11 complex promotes mitochondrial fission by interacting with DNM1. Differently, in fission yeast, it has been found that another OMM protein, named ATG43, might function as a mitophagy receptor by coordinating with the mitochondrial import factors instead [ 46 ].…”
Section: Mitophagy: More Than One Way To Get Rid Of a Mitochondriomentioning
confidence: 99%
“…( B ) In budding yeast, the only identified receptor is ATG32, which is phosphorylated and recognized by ATG11 or ATG8 respectively [ 42 , 43 , 44 , 45 ]. Another mitochondrial outer membrane protein, ATG43, serves as the mitophagy receptor in fission yeast [ 46 ]. However, the function of cardiolipin is not clear in yeast mitophagy.…”
Section: Figurementioning
confidence: 99%
“…As in S. cerevisiae , nitrogen starvation induced autophagic elimination of mitochondria in this fission yeast, but the molecular mechanism underlying this degradation, and whether this pathway is selective to mitochondria, remains uncertain [ 93 , 94 ]. In their recent work, Fukuda et al (2020) identified the protein Atg43 as a new mitophagy receptor in S. pombe [ 95 ].…”
Section: Mitophagy In Other Yeast Speciesmentioning
confidence: 99%